Tabula Raja: Mapping race and human diversity in American genome science - Fullwiley, Duana (California California University Press, 2024)
Duana Fullwiley has penned an intimate chronicle of laboratory life in the genomic age. She presents many of the influential scientists at the forefront of genetics who have redefined how we practice medicine and law and understand ancestry in an era of big data and waning privacy. Exceedingly relatable and human, the scientists in these pages often struggle for visibility, teeter on the tightrope of inclusion, and work tirelessly to imprint the future.